Are semi-terrestrial crabs threatened by human noise? Assessment of behavioural and biochemical responses of Neohelice granulata (Brachyura, Varunidae) in tank. (December 2018) - Filiciotto, Francesco; Sal Moyano, María Paz; de Vincenzi, Giovanni; Hidalgo, Fernando; Sciacca, Virginia; Bazterrica, Maria Cielo; Corrias, Valentina; Lorusso, Martìn; Mazzola, Salvatore; Buscaino, Giuseppa; Gavio, María Andrea
Abstract: This study examined the effects of human lab-generated noise (sweep tone) on the behaviour and biochemistry of a semi-terrestrial crab ( Neohelice granulata ). The experiment was carried out in tanks equipped with video- and audio-recording systems on a total of seventy-eight specimens. In total, 42 experimental trials with sweep-tone exposure and control conditions were performed using crabs in single and group layouts. After a habituation period of 30 min, the locomotor and acoustic (sound signals emitted by the crabs) behaviours were monitored for 30 min. During this time, the animals in sweep-tone conditions were exposed to ascending sweeps in a bandwidth range of 2.5–25 kHz. Exposure to sweep-tone noise produced significant changes in the number of signals emitted, locomotor behaviours and plasma parameters, such as haemolymph total haemocyte count and glucose, lactate and total protein concentrations, revealing that human noise could represent a disturbance for this crustacean species. Highlights: This study evaluated the effects of noise pollution on the behaviour and biochemistry of the crab Neohelice granulata . The acoustic emissions of grouped specimens were significantly affected by the noise. Locomotor behaviours of single and grouped specimens showed changes in the presence of noise. Plasma parameters of single and grouped specimens were significantly changed in the presence of noise. Noise pollution could play a threatening role for this semi-terrestrial crab.